"Drinking in the Dark" (DID): A Simple Mouse Model of Binge‐Like Alcohol Intake. Issue 1 (1st July 2014) - Thiele, Todd E.; Crabbe, John C.; Boehm, Stephen L.
Abstract: One of the greatest challenges that scientists face when studying the neurobiology and/or genetics of alcohol (ethanol) consumption is that most preclinical animal models do not voluntarily consume enough ethanol to achieve pharmacologically meaningful blood ethanol concentrations (BECs). Recent rodent models have been developed that promote binge‐like levels of ethanol consumption associated with high BECs (i.e., ≥100 mg/dl). This unit describes procedures for an animal model of binge‐like ethanol drinking which has come to be called "drinking in the dark" (DID). The "basic" variation of DID involves replacing the water bottle with a bottle containing 20% ethanol for 2 to 4 hr, beginning 3 hr into the dark cycle, on cages of singly‐housed C57BL/6J mice. Using this procedure, mice typically consume enough ethanol to achieve BECs >100 mg/dl and to exhibit behavioral evidence of intoxication. An alternative two‐bottle (ethanol and water) procedure is also described. Curr. Protoc. Neurosci . 68:9.49.1‐9.49.12. © 2014 by John Wiley & Sons, Inc.